Sdgs Compas of Pupuk Indonesia Holding Company: Analysing the Performance of Sustainability Reports - Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2023)
Purpose: This study aims to analyze the performance of Pupuk Indonesia's Sustainability Report in relation to its contribution to the Sustainable Development Goals (SDGs). Specifically, it examines the suitability of the company's report disclosures based on the GRI Standards to demonstrate its SDG contributions. Method: The study employs a postmodernist approach, utilizing explorative dialogue as its primary methodology. Data was collected from Pupuk Indonesia's official sustainability reports published between 2019 and 2021. These reports were then analyzed through a constructed dialogue between an "SDGist" and a "Sustainability Report Assuror." Findings: The study reveals that Pupuk Indonesia strongly commits to the SDGs through its overall activities and Corporate Shared Values (CSV). The company's contribution to the SDGs has increased over the analyzed period: 33.67% in 2019, 33.89% in 2020, and 40.77% in 2021. Pupuk Indonesia exhibits particularly strong contributions to seven key SDGs: Good Health and Well-being, Quality Education, Affordable and Clean Energy; Decent Work and Economic Growth; keeping Marine Ecosystems, Keeping Land Ecosystems, and Peace, Justice, and Strong Institutions; and Partnerships to Achieve the Goals. Practical Implications: This research provides valuable insights for Pupuk Indonesia to enhance its sustainability reporting and strengthen its alignment with the SDGs. The findings can also serve as a benchmark for other companies in the sector to assess and improve their sustainability performance and reporting practices. Originality: The study's unique contribution lies in applying postmodernist explorative dialogue to analyze the relationship between sustainability reporting and SDG contributions. This novel approach provides a deeper understanding of the underlying narratives and interpretations within the company's sustainability discourse. Paper Type: This research can be categorized as a qualitative Keywords: Pupuk Indonesia, SDGs, Sustainability Report, CSV